Sistem ekonomi humanistik versus pasar bebas (Studi kasus kebijakan penanganan kemiskinan di Indonesia) - Minanda, Evy Flamboyan (Institute for Advanced Science, Social, and Sustainable Future, 2024)
A country's economic policies lead to poverty, and the policies of other sectors, such as the economy, labor, education, and health, should help address poverty. Although poverty is influenced by many factors, it is not an independent factor. Fully recognized by our founders, our constitution, the 1945 Constitution of the Republic of Indonesia (UUD 1945) included provisions on the National Economy and Social Welfare in Chapter XIV. The Indonesian Constitution has chosen an economic system that is in accordance with the basic norms of the Indonesian nation, namely the Pancasila economic system which is then called the humanistic economic system, especially in relation to poverty policy in Indonesia.